Geographic Variation in Inpatient Care Utilization, Outcomes and Costs for Dementia Patients in China - Zhuoer Lin; Fang Ba; Heather Allore; Gordon G. Liu; Xi Chen (Global Labor Organization (GLO), 2022)
Dementia leads public health issue worldwide. China has the largest population of adults living with dementia in the world, imposing increasing burdens on the public health and healthcare systems. Despite improved access to health services, inadequate and uneven dementia management remains common. We document the provincial-level geographic patterns in healthcare utilization, outcomes, and costs for patients hospitalized for dementia in China. Regional patterns demonstrate gaps in equity and efficiency of dementia care and management for dementia patients. Health policy and practices should consider geographic disparities in disease burden and healthcare provision to promote equitable allocation of resources for dementia care throughout China.
Keywords: J14; I11; I14; I18; H75; 330; Dementia; Health Care; Hospitalization; Inpatient Costs; In-hospital Mortality; Geographic Variation